2018
DOI: 10.3389/fimmu.2018.02975
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Cytokine and Chemokine Profiles in Individuals With Schistosoma mansoni Infection and Low Parasite Burden

Abstract: Intestinal schistosomiasis, caused by the parasitic trematode Schistosoma mansoni, is a chronic disease and the prolonged and continuous exposure to S. mansoni antigens results in a deviation of the host's immune response. For diagnosis, the Kato-Katz (KK) method is recommended, however, this method showed low accuracy in areas of low endemicity. This study aimed to characterize the cytokine and chemokine profile of individuals with an extremely low parasite load (<4 eggs per gram of feces), e.g., individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…However, the cytokine expression profile of PBMCs following PZQ therapy shows a mixed Th1/Th2/Th17 response with nearly all of the cytokines measured were upregulated compared to the cytokine profile at week 13 with the exceptions of TGFβ being downregulated and TNF-α and IL-6 showing no significant change. Destruction of the adult schistosome worm releases antigens that may be concealed from the host immune response, such as antigens in the tegument, thus causing a strong cellular immune response, although marked variability of cytokine expression between individuals can exist (Joseph et al, 2004a;Martins-Leite et al, 2008;Castro et al, 2018; Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytokine expression profile of PBMCs following PZQ therapy shows a mixed Th1/Th2/Th17 response with nearly all of the cytokines measured were upregulated compared to the cytokine profile at week 13 with the exceptions of TGFβ being downregulated and TNF-α and IL-6 showing no significant change. Destruction of the adult schistosome worm releases antigens that may be concealed from the host immune response, such as antigens in the tegument, thus causing a strong cellular immune response, although marked variability of cytokine expression between individuals can exist (Joseph et al, 2004a;Martins-Leite et al, 2008;Castro et al, 2018; Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, the broad stimulus of the mitogen may recover the cellular memory immune response generated during the larval (acute) and egg (chronic) deposition phases. The production of type 1 cytokines, TNF-a, IL-6, IFN-c, with or without IL-10, by whole blood or mononuclear cells, has been reported in loads parasites above 100 epg faeces, present in the acute phase [27,[46][47][48], whereas, the IL-10 is marker of the Th2/Treg profile induced by soluble antigens of S. mansoni eggs [49,50]. In addition to IL-10, infection by S. mansoni induces regulatory factors such as Tregs cells, TGF-b and CTLA-4 in the modulation of the inflammatory response in allergy [2,51].…”
Section: Discussionmentioning
confidence: 99%
“…The airway epithelial cells of children with a history of wheezing demonstrate reduced CCL5, CCL2 and IL-6 [26]. Recently, it was reported that, in the context of infection with S. mansoni with or without allergic reactivity (anti-allergen IgE in serum), there was no difference in the levels of the chemokines CCL3, CCL5, CXCL10 or CCL11 [27,28]; however, there was an increase in plasma CXCL8 levels during acute S. mansoni infection [29]. These studies showed no correlation with allergy symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The association of CCL17 and eosinophilia with S. mansoni infection was not unexpected, since these mediators are markers of a type-2 immune response, which is frequently reported in helminth-infected individuals ( 15 , 16 ). Activated eosinophils are an important source of IL-4, IL-5, and IL-13 ( 62 , 63 ), and this environment induces the production of CCL17 ( 64 ), which is described as a signature chemokine of helminth infection, especially S. mansoni , in humans ( 49 , 65 ). Moreover, Jakubzick et al ( 66 ) demonstrated that CCL17 production participates in CCR4 + -cell recruitment to S. mansoni -induced lung granulomas, stimulating Th2 inflammatory markers, and increasing the hydroxyproline content in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected in the morning after fasting and using EDTA-containing tubes for a complete blood count performed by a commercial local laboratory and EDTA-free tubes to obtain the serum for immunological analysis, as previously detailed ( 41 , 49 ). In the current work, data on hemoglobin levels and the number of circulating red blood cells, eosinophils, and platelets were evaluated as the median value and as frequency of altered values among individuals with different infection status.…”
Section: Methodsmentioning
confidence: 99%